The Impact of COVID-19-Pandemic on Psychological Health and Educational Status of the Dental Students from the Instructor and Student’s Viewpoints - Shakir, Abdullah (Pegem eğitim ve öğretim dergisi = Pegem journal of education and instruction, 2023)
The present cross-sectional study aimed to investigate the dentistry teaching staff as well as psychological health and educational status of students who experienced the lockdown last year in Iraqi colleges. The study participants were divided into two groups: the first group included a total of 1250 participants from 28 different colleges of dentistry (public and private), who answered the questionnaire with a response rate of 71.76%; the second group included a total of 776 students (474 females and 302 males) with a gender ratio of 1.6:1. The results showed that COVID-19 pandemic lockdown affected the academic performance of most participants (82.2%) with varying degrees. Overall, the mean evaluation score for online education was 31.3±6.9, while that for the practical subjects was 68.6%±6.9. Although online education provided the students with an opportunity for self-study, it faced a serious challenge when offering the students the practical subjects in medical science. Since majority of the courses in medical science included practical subjects, the students experienced real difficulties receiving online education.